Factors That Affecting Stock Returns in LQ45 Companies on The Indonesia Stock Exchange - Feri Noviyanti; Dewi Sarifah Tullah (Universitas Medan Area, 2022)
Stock return is the level of profit obtained by investors on their investment. Through signal theory, companies can give signals to investors for their actions which will have an impact on stock returns. The aims of this study were to determine the effect of Beta, ROA, CR, PBV and MVA on stock returns. This study uses the LQ-45 Index company as the population and purposive sampling in the sampling technique, with the criteria that the company publishes financial statements on the Indonesia Stock Exchange from the year of 2001-2020. Analysis using panel data regression. Research proves that ROA, PBV and MVA variables can affect stock returns, while for beta and CR variables it is proven not to affect stock returns. Investors in investing should pay attention to the value of the ROA, PBV and MVA ratios in the company that is the target of their investment, because these ratios are proven to affect stock returns.